Evaluación del uso de la Cascarilla de Arroz en la Fabricación de Bloques de Concreto - Molina-Salas, Esteban (Instituto Tecnológico de Costa Rica, 2010)
The housing projects, that had development by governmental institute, such as INVU, whose carried out researches about to improve building system, with the objective to create system of lightweight concrete blocks, which were greater density than the system of regular block. This study took the initiative to develop an analysis of the use to rice husks in the manufacture of stone blocks; took into account, the availability of the rice industry would supply raw materials and developing a mix design for the manufacturing of the blocks.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2010.
Keywords: Cerámicos; Sustituto; Sustrato hidropónico; Concreto ligero; Agregados; Compresión